2012
DOI: 10.1038/aps.2011.162
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin prevents the mutant huntingtin-suppressed GLT-1 expression in cultured astrocytes

Abstract: Aim: To investigate the effects of rapamycin on glutamate uptake in cultured rat astrocytes expressing N-terminal 552 residues of mutant huntingtin (Htt-552). Methods: Primary astrocyte cultures were prepared from the cortex of postnatal rat pups. An astrocytes model of Huntington's disease was established using the astrocytes infected with adenovirus carrying coden gene of N-terminal 552 residues of Huntingtin. The protein levels of glutamate transporters GLT-1 and GLAST, the autophagic marker microtubule-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…3NP was shown to induce an increase in intracellular Ca 2+ in cultured astrocytes which was due to an influx of Ca 2+ by the reverse operation of the Na + -Ca 2+ exchanger, possibly explaining the gliotoxic action of 3NP (225). HD has also been examined in cultured astrocytes infected with an adenovirus carrying the coden gene of N-terminal 552 glutamine repeats (226). In these cells the GLT-1 glutamate transporter and glutamate uptake were found to be significantly reduced.…”
Section: Discoveries Made By Employing Primary Cultures To Understandmentioning
confidence: 99%
“…3NP was shown to induce an increase in intracellular Ca 2+ in cultured astrocytes which was due to an influx of Ca 2+ by the reverse operation of the Na + -Ca 2+ exchanger, possibly explaining the gliotoxic action of 3NP (225). HD has also been examined in cultured astrocytes infected with an adenovirus carrying the coden gene of N-terminal 552 glutamine repeats (226). In these cells the GLT-1 glutamate transporter and glutamate uptake were found to be significantly reduced.…”
Section: Discoveries Made By Employing Primary Cultures To Understandmentioning
confidence: 99%
“…Another potential mechanism involves direct effects of mTOR inhibitors on astrocytes and GLT‐1 glutamate transporter expression. For example, recent evidence indicates that rapamycin can upregulate GLT‐1 expression …”
Section: Discussionmentioning
confidence: 99%
“…If GLAST can cope and compensate for the failure of GLT‐1, it might be a possible target for future therapeutic approaches. Interestingly, studies in primary astrocyte cultures from cortex demonstrated that expression of mHtt in astrocytes significantly decreased both mRNA and protein levels of GLT‐1 but not those of GLAST …”
Section: Discussionmentioning
confidence: 99%